Computer Anxiety and Skills amongst Undergraduate Students from Rural Areas - Nor Al-Ashekin Wan Husin, Wan; Thinakaran, Rajermani; Zakiyatussariroh Wan Husin, Wan (International Journal of Engineering and Technology, 2018)
With the rapid growth of technology, nowadays people are using Information Communication Technology (ICT) as a tool in all aspects of life. Malaysia towards Vision 2020 has implemented many initiatives in ICT transformation for community including students from the rural areas. This study is conducted to examine computer level of anxiety and skills amongst undergraduate students from rural areas at selected private higher institutions in Negeri Sembilan. The study was done through distribution of 128 questionnaires to year one students from non-computing programs who are enrolled computer literacy subject at the institutions. The findings of this study show that the level of anxious on using computer amongst undergraduate students is low. The students also show a good level of computer skills but low level of web site development skills. It is recommended that any web site development training for rural areas students should take into consideration for studentâ€™s enhancement and career. Future study on web site development skills amongst undergraduate students from rural areas at higher institution also is recommended.Â